The effect of rheumatoid arthritis on patient-reported outcomes following knee and hip replacement: evidence from routinely collected data - Burn, E; Edwards, C; Murray, D; Silman, A; Cooper, C; Arden, N; Pinedo Villanueva, P; Prieto Alhambra, D (Oxford University Press, 2019)
Objectives To compare outcomes of total knee replacement (TKR) and total hip replacement (THR) for individuals with RA and OA. Methods We performed a cohort study using routinely collected data. Oxford Knee Score, Oxford Hip Score, and EuroQol 5-dimension 3-level (EQ-5D-3L) questionnaires were collected before and 6 months after surgery. Multivariable regressions were used to estimate the association between diagnosis and post-operative scores after controlling for pre-operative scores and patient characteristics. Results Study cohorts included 2070 OA and 142 RA patients for TKR and 2030 OA and 98 RA patients for THR. Following TKR, the median Oxford Knee Score was 37 [interquartile range (IQR) 29–43] for OA and 36 (27–42) for RA while the median EQ-5D-3L was 0.76 (0.69–1.00) and 0.69 (0.52–0.85), respectively. After THR, the Oxford Hip Score was 42 (IQR 36–46) for OA and 39 (30–44) for RA while the EQ-5D-3L was 0.85 (0.69–1.00) and 0.69 (0.52–1.00), respectively. The estimated effect of RA, relative to OA, on post-operative scores was −0.05 (95% CI −1.57, 1.48) for the Oxford Knee Score, −0.09 (−0.13, −0.06) for the EQ-5D-3L following TKR, −1.35 (−2.93, −0.22) for the Oxford Hip Score, and −0.08 (−0.12, −0.03) for the EQ-5D-3L following THR. Conclusion TKR and THR led to substantial improvements in joint-specific scores and overall quality of life. While diagnosis had no clinically meaningful effect on joint-specific outcomes, improvements in general quality of life were somewhat less for those with RA, which is likely due to the systemic and multijoint nature of rheumatoid disease.